STRATEGI KEPALA SEKOLAH DAN GURU DALAM MEMBENTUK KARAKTER PESERTA DIDIK MELALUI PANCA KARAKTER - Fina Mawadatul ‘Ulya; Imron Arifin; Ali Imron; Achmad Supriyanto; Fina Mawadatul ‘Ulya; Imron Arifin; Ali Imron (Universitas Negeri Malang, 2024)
Abstract: The objective of this research is to describe in detail the strategies of principals andteachers in shaping the character of students through the panca karakter in SD AnakSaleh Malang, starting from the strategies of the principal and teachers in shapingthe character of students, implementing panca karakter to shape the character ofthe participants. students, the implementation of strategies in shaping thecharacter of students through panca karakter, and the results of implementingstrategies to shape the character of students through panca karakter. This researchuses a qualitative approach with descriptive research type. The results of thisresearch are strategies to shape the character of students by approaching children,touching the child's heart, doing habituation, and providing examples or rolemodels for students. The panca karakter consist of personal, social, intellectual,natural and national piety. 5 educations based on panca karakter to form charactersconsisting of KPBS, TTM, Green Force, KANCIL, Home Base System. Supportingfactors for the implementation of character education are school facilities, teachingstaff and education, character building. Inhibiting factors in the environmentoutside of school, including family. The solution is by holding parenting, workshops,home visits, and calling parents. The characters that stand out a lot after theimplementation of character education are more personal piety, social piety, andnational piety.